Sistem Informasi Logbook Pegawai Politeknik Negeri Cilacap Sebagai Absensi Online Pada Masa Pandemi COVID-19 - Nur Wachid Adi Prasetya; Prih Diantono Abda’u; Muhammad Nur Faiz; Annas Setiawan Prabowo (Universitas Muhammadiyah Purworejo, 2021)
Politeknik Negeri Cilacap as an educational institution under The Ministry of Education of The Republic of Indonesia has adopted the Work From Home (WFH) policy to suppress the spread of COVID-19. In the implementation of WFH, lecturers and employees are required to make reports. The mechanism of this report has problems, including a lack of standardized report forms, obstructed work report (logbook) approval processes by the unit’s leader, and reports that are still in Microsoft Excel files, making it difficult for the staffing department to map and calculate the employee's attendance. The purpose of this research is to design and build a logbook information system for Politeknik Negeri Cilacap that is used for online employee attendance during the COVID-19 pandemic. This research uses the Waterfall method as a system development method, with Unified Modeling Language (UML) as a design model. The result of this research is a logbook information system that was built as a tool for lecturers and employees to report their activities, and for staffing department to monitor and appraise employee performance. Based on the usability test result, this system has a 78.61% value and a “Good” predicate.